POTRET PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA TEAM LEADER PEMBUKAAN REKENING ONLINE PADA PT BANK CENTRAL ASIA TBK. DI KABUPATEN TANGERANG - Yosandra Tan Wijaya; Abdul Azis (Jurnal Menara, 2026)
This study aims to determine the potrait of career development and motivation on the performance of Team Leaders in Online Account Opening at PT Bank Central Asia Tbk in Tangerang. This research employs a quantitative method. The population in this study consisted of all Team Leaders of online account opening, with a sample of 74 respondents. The data analysis techniques used were simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination, and hypothesis testing. The results show that career development has a significant effect on employee performance, with the simple linear regression equation Y = 10.472 + 0.795X1. The correlation coefficient value between career development and performance is 0.767, indicating a strong relationship, with a coefficient of determination (R Square) of 0.589. Hypothesis testing indicates that tcount > ttable (10.152 > 1.99346), so H₀₁ is rejected and H₁ is accepted. Motivation also significantly influences performance with the simple linear regression equation Y = 7.702 + 0.823X2. The correlation coefficient value is 0.800 with an R Square of 0.640. The tcount = 11.304 > 1.99346, meaning H₀₂ is rejected and H₂ is accepted. Simultaneously, career development and motivation significantly affect performance with the multiple linear regression equation Y = 3.855 + 0.403X1 + 0.528X2. The correlation coefficient value of 0.862 indicates a very strong relationship, with an R Square of 0.700 or 70%. The F-test shows that Fcount > Ftable (86.313 > 3.126), thus H₀₃ is rejected and H₃ is accepted. Therefore, it can be concluded that career development and motivation have a positive and significant effect on the performance of Team Leaders in Online Account Opening at PT Bank Central Asia Tbk in Tangerang.